A comprehensive simulation study of a network-based distributed mobility management framework. (2016) - Murtadha, Muayad Khalil; Noordin, Nor Kamariah; Ali, Borhanuddin Mohd; Hashim, Fazirulhisyam
New mobility solutions are required for mobile environments characterised by an ever-increasing number of mobile devices and volume of internet data traffic. A single mobility anchor in the current Centralised Mobility Management (CMM) performs all mobility and routing functionalities. Distributed Mobility Management (DMM) paradigm is introduced recently to overcome scalability, reliability and non-optimal routing issues of the CMM. The DMM approach is proposed to flatten the network architecture by moving the mobility anchors closer to the users and separating the control and data planes at the network edge. In this paper, we develop and implement a network-based DMM model using NS2 simulation tool. Extensive simulations are performed to evaluate the performance of the DMM against that of the CMM. The simulation results indicate that the DMM approach outperforms the CMM approach under various mobility environments. Thus, this study verifies previous analytical studies and provides more accurate findings in DMM.